If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9x = 6x + 42 Combine like terms: 3x + 9x = 12x 12x = 6x + 42 Reorder the terms: 12x = 42 + 6x Solving 12x = 42 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12x + -6x = 42 + 6x + -6x Combine like terms: 12x + -6x = 6x 6x = 42 + 6x + -6x Combine like terms: 6x + -6x = 0 6x = 42 + 0 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| 9b+3b=144 | | 1/6X=-3. | | -2.3x-4.2x=-66.3 | | 5f-2.2=-2.5 | | x+22=-8 | | 3(x+2)-2x=2x-2 | | x-1/-4=2/3 | | 2(-3y+180)+y=180 | | -3n+8n=16+n | | 12x-3+7x-2=90 | | 1/3x-7=17 | | 19x=39 | | 47.5x=14x+2x^2 | | 4(a+2)=12-2(3-2a) | | (3a-7b+8c)+(a-9b+10c)+(-9+8b-11c)= | | -7+n(10.5-2.5)= | | 9y+5=104 | | 6y+20=2g+32 | | -7-n(10.5-2.5)= | | 12p-8=22+20p | | 6(x-5)-(5x-9)=8 | | -7-13n= | | -x+150-2x=30 | | 14=21m | | 2ax^2-2x-2a=0 | | 2y+1+8y=21 | | 9-5n=75 | | -5w+-24=11 | | 9n=24 | | -5w+-24=1 | | k/8=-2/5 | | -7+8n= |